Anti-emetic Drugs for Prophylaxis of Postoperative Nausea and Vomiting After Craniotomy: An Updated Systematic Review and Network Meta-Analysis - Chen, Yijing; Chang, Jing (Frontiers in Medicine, 2020)
Background: There is uncertainty about the the effect of antiemetic drugs (AEDs) for the prophylaxis of postoperative nausea and vomiting (PONV) after craniotomy. We assessed the efficiency and safety of antiemetic drugs for postoperative nausea and vomiting. Methods and findings: We searched online databases including the Cochrane Library, PubMed, Wiley, Elsevier Science Direct, Ovid LWW, and Springer from 1985 to June 2018. Adults undergoing craniotomy with the prophylactic use at least one AED were included. The primary outcomes were the incidence of postoperative nausea (PON) and postoperative vomiting (POV) during the first and second day. A total of 1433 participants spanning seventeen clinical trials were enrolled onto this Network Meta-Analysis (NMA). Compared to placebo, there was a 69.2% probability that ramosetron (OR: 0.063, 95% Crl: 0.0064-0.45) was the most effective treatment for 24 hours after surgery on PON. For POV, droperidol (OR=0.029, 95% Crl: 0.0025-0.25) was the best treatment for POV during the first 2 hours with a possibility of 71.1%, fosaprepitant (24h: OR= 0.027, 95% Crl: 0.0068-0.094; 48h: OR=0.036, 95% Crl: 0.0062, 0.18) deemed the most efficacious treatment for 24 hours (probability 66.9%) and 48 hours (probability 56.6%) postoperatively. Besides, ramosetron showed a significantly higher incidence of complete responses (OR=29. 95% Crl: 6.5e+02) as well as lower rescue AED requirement (OR=0.022, 95% Crl: 0.0006-0.20). Granisetron was associated with the lowest incidence of headache and excessive sedation outcome. Conclusions: Compared with placebo, ramosetron is the best prophylaxis option on PON 24 hours after craniotomy with higher complete responses. Besides fosaprepitant was considered the most effective prophylaxis option for POV on the first and second postoperative days. All these findings should be better applied in combination with perioperative dexamethasone. These findings may offer suggestions for the clinician to provide more targeted prophylaxis approach on drug therapy with fewer adverse effects.